2012
DOI: 10.1016/j.ssresearch.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and beliefs about national development and developmental hierarchies: The viewpoints of ordinary people in thirteen countries

Abstract: Scholars and policy makers have for centuries constructed and used developmental hierarchies to characterize different countries. The hypotheses motivating this paper are that such social constructions have been circulated internationally, are constructed similarly in various countries, and follow the social constructions of elite international organizations, such as the United Nations. This paper uses data from fifteen surveys in thirteen diverse countries to study how developmental hierarchies are understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 30 publications
8
69
1
Order By: Relevance
“…Thornton and his colleagues (2012a) used data from fifteen surveys in thirteen diverse countries to show that ordinary people in each setting understand developmental hierarchies and can use this understanding to rate a series of countries on development. In addition, large percentages of people in these thirteen countries rate countries on development similarly to the development ratings of the UN HDI, suggesting that development is not only widely understood, but understood in ways that are similar to the perspectives of international elites (Binstock and Thornton 2007, Melegh, et al 2012, Thornton, et al 2012, Xie, et al 2012 This body of research has also shown that while views of development and developmental hierarchies are widespread among individuals in many countries, there is also considerable variability in the ways people perceive development (Thornton, et al 2012). This is demonstrated in the fact that significant proportions of people either do not subscribe to developmental hierarchies or define them differently than does the United Nations and other international elites.…”
Section: Conceptual Backgroundmentioning
confidence: 92%
See 2 more Smart Citations
“…Thornton and his colleagues (2012a) used data from fifteen surveys in thirteen diverse countries to show that ordinary people in each setting understand developmental hierarchies and can use this understanding to rate a series of countries on development. In addition, large percentages of people in these thirteen countries rate countries on development similarly to the development ratings of the UN HDI, suggesting that development is not only widely understood, but understood in ways that are similar to the perspectives of international elites (Binstock and Thornton 2007, Melegh, et al 2012, Thornton, et al 2012, Xie, et al 2012 This body of research has also shown that while views of development and developmental hierarchies are widespread among individuals in many countries, there is also considerable variability in the ways people perceive development (Thornton, et al 2012). This is demonstrated in the fact that significant proportions of people either do not subscribe to developmental hierarchies or define them differently than does the United Nations and other international elites.…”
Section: Conceptual Backgroundmentioning
confidence: 92%
“…A recent but growing body of survey research has documented that the ideas of development and developmental hierarchies are widespread in many parts of the world (Binstock and Thornton 2007, Melegh, et al 2012, Thornton, et al 2012, Xie, et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory also implies that persons living in less-developed societies would be better off if they adopted the family behaviors and values prevalent in more developed societies. Studies of both developed and developing countries show that marriage, childbearing, and other family behaviors have been influenced by the forces of developmental idealism (Abbasi-Shavazi and Askari-Nodoushan 2012; Gerber and Berman 2010; Thornton et al 2012; Thornton and Philipov 2009). For instance, analyzing data from the US, Egypt, Iran, Nepal, Argentina, and China, Thornton and Philipov (2009) found widespread belief in the mutual linkage between levels of fertility and socioeconomic development.…”
Section: Cohabitation As a Form Of Unionmentioning
confidence: 99%
“…Within that field of analysis targeting the implications of otherness, orientalism, or coloniality of power in East Central Europe, this paper stands closest to analyses that focus on specific regional constellations of intersections between structural integration and symbolic hierarchies. These include "nesting orientalisms" in Bakić-Hayden (1995), "nesting Colonialisms" in Petrović (2008), "European rule of difference" and "moral geopolitics" in Böröcz (2006), as well as the "East-West slope" in Melegh (2006), the empirical demonstration of correspondence between perceptions of national development and global developmental hierarchies in Thornton et al (2012), the "moral regulation of the Second Europe" in Arfire (2011), or the differentiation between "exotic other" and "stigmatized brother" in Buchowski (2006). It also stands close to works which describe internal political cleavages in relation to external structures of integration (e.g.…”
mentioning
confidence: 99%